2018
DOI: 10.1080/14656566.2018.1517155
|View full text |Cite
|
Sign up to set email alerts
|

Current and emerging pharmacotherapy for prediabetes: are we moving forward?

Abstract: Prediabetes is a state wherein blood glucose levels are above normal but below the diagnostic threshold for diabetes. Seventy percent of patients with prediabetes develop type 2 diabetes in their lifetime. Despite this, prediabetes frequently goes undiagnosed. Areas covered: This review focuses on the pharmacological treatment of prediabetes and the prevention of progression to diabetes. A literature search was carried out on PubMed and Embase to review randomized controlled trials examining treatment of predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Considering the high prevalence of prediabetes, and the robust and significant association between prediabetes and health risk shown in our study, successful intervention in this large population could have a major effect on public health. Although prediabetes is commonly asymptomatic, it represents a window of opportunity to prevent progression to type 2 diabetes and its complications 33. Community mobilisation and lifestyle intervention for prediabetes can lead to a significant reduction in the incidence of diabetes 2934.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the high prevalence of prediabetes, and the robust and significant association between prediabetes and health risk shown in our study, successful intervention in this large population could have a major effect on public health. Although prediabetes is commonly asymptomatic, it represents a window of opportunity to prevent progression to type 2 diabetes and its complications 33. Community mobilisation and lifestyle intervention for prediabetes can lead to a significant reduction in the incidence of diabetes 2934.…”
Section: Discussionmentioning
confidence: 99%
“…Although prediabetes is commonly asymptomatic, it represents a window of opportunity to prevent progression to type 2 diabetes and its complications. 33 Community mobilisation and lifestyle intervention for prediabetes can lead to a significant reduction in the incidence of diabetes. 29 34 Follow-up studies from the Diabetes Prevention Programme have shown that lifestyle intervention can be cost effective in preventing diabetes, and that treatment with metformin can even be cost saving.…”
Section: Discussionmentioning
confidence: 99%
“…Prediabetes is a toxic state in which both micro-and macrovascular complications of diabetes can manifest [6]. The prompt diagnosis and proper management of prediabetes are necessary to prevent progression to diabetes mellitus and to prevent microvascular and macrovascular complications that manifest early in the prediabetic state [7].…”
Section: Introductionmentioning
confidence: 99%
“…The National Institute for Health and Care Excellence (NICE) guidelines suggest that individuals with IGT or IFG should firstly receive lifestyle intervention by increasing physical activity, reducing body weight, and health education. [4] Specifically, people with prediabetes should exercise for no less than 150 min/week and cut down 5%-10% of body weight within a year. [18] Similar suggestions are given by other guidelines from the American Diabetes Association (ADA) that patients should perform a high-intensity exercise at 200-300 min/week and eat a very low-calorie diet (500-750 kcal/day) for 3 months to achieve a weight loss of >5%.…”
Section: Lifestyle Interventionmentioning
confidence: 99%
“…[3] Due to the ambiguity of diagnostic criteria and thresholds, asymptomatic prediabetes is likely to be ignored and evolves into T2D. [4] JOURNAL OF TRANSLATIONAL INTERNAL MEDICINE / JUL-SEP 2020 / VOL 8 |ISSUE 3…”
Section: Introductionmentioning
confidence: 99%